2022
DOI: 10.1111/jth.15740
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor propeptide variants lead to impaired storage and ER retention in patient‐derived endothelial colony‐forming cells

Abstract: Background von Willebrand factor (VWF) is synthesized by vascular endothelial cells and megakaryocytes. The VWF propeptide is critical for multimerization and acts as an intra‐molecular chaperone for mature VWF in sorting to its storage organelles, Weibel‐Palade bodies (WPBs). In the Canadian Type 3 VWD study, almost half of the identified variants were in the VWF propeptide and these were associated with an increased bleeding phenotype. Objective To investigate VWF propeptide variants that cause quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…This process is believed to inhibit platelet recruitment and other responses of the host coagulation cascade by shrouding the bacteria in host vWF. Or, conversely, a previous paper report by Gaytán et al [ 181 ] showed that a new adhesin that binds to sialic acid is crucial for infective endocarditis in several bacterial species. However, it is unclear how this relates to enterococcal endocarditis.…”
Section: Point and Counterpointmentioning
confidence: 94%
“…This process is believed to inhibit platelet recruitment and other responses of the host coagulation cascade by shrouding the bacteria in host vWF. Or, conversely, a previous paper report by Gaytán et al [ 181 ] showed that a new adhesin that binds to sialic acid is crucial for infective endocarditis in several bacterial species. However, it is unclear how this relates to enterococcal endocarditis.…”
Section: Point and Counterpointmentioning
confidence: 94%
“…VWF, VE-Cadherin, and nuclear staining was performed as described previously. 19 The coverslips were then mounted to slides using antifade mounting medium (Vecta-Sheild) and imaged using a Leica TCS SP8 confocal fluorescence microscope and the LASX software (Leica Microsystems). Images were taken by a blinded microscopist.…”
Section: Methodsmentioning
confidence: 99%
“…Confocal immunofluorescence microscopy: For confocal immunofluorescence (IF) microscopy, the stimulation protocol was performed as described above with the exception that collagen coated coverslips were added to the wells and cells seeded to these. VWF, VE-Cadherin, and nuclear staining was performed as described previously 19 . The coverslips were then mounted to slides using anti-fade mounting medium (Vecta-Sheild) and imaged using a Leica TCS SP8 confocal fluorescence microscope and the LASX software (Leica Microsystems).…”
Section: Stimulation Of Ecfcsmentioning
confidence: 99%
“…The data obtained from these studies led to the discovery the novel pathogenesis mechanisms leading to VWF deficiencies in VWD patients and clarifying the effect of VWF variants on intracellular processing of VWF, including multimerization, storage/formation of WPBs, and secretion. 22,[44][45][46][47][48][49][50][51] The use of the patient-derived ECFCs emphasized the significance of the exonic synonymous and deep intronic variants on VWF splicing and their contribution to the pathogenesis of VWD. [44][45][46][47]51 Furthermore, we inspected the gene expression profile and trafficking of the inflammatory/angiogenesis proteins Ang2 and P-selectin, co-stored with VWF in WPBs, in the patient-and healthy control-derived ECFCs.…”
Section: Bleeding Disorder: Vwdmentioning
confidence: 99%